Dampak Kaderisasi terhadap Organisasi MWC NU Rowokele - Muna Fauziah; Bahrun Ali Murtopo; Nur Zakaria; Linda Maghfiroh (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2022)
This article is community service-based research with the aim of describing the impact of cadre formation on the MWC NU Rowokele organization. A qualitative approach is used to describe the content of Community Service. The service is located at MWC NU Rowokele. The data collection technique was carried out by conducting interviews with the Chairman of Tanfidziyah MWC NU Rowokele. Data were analyzed using data collection techniques, data reduction, data presentation, and drawing conclusions. The results of the dedication show that the presence of cadres has not had a good impact on the development of the MWC NU Rowokele organization. This is because the MWC NU Rowokele has not run well, the management does not have a special technique for recruiting the latest cadres, and the limited number of MWC staff who are truly willing to build a better MWC. Thus, suggestions are addressed to the management of MWC NU Rowokele to actively cooperate with each branch so that MWC has a broad view of the cadres that are formed from each activity in the MWC NU Rowokele Branch.